Interaction between Gravitropism and Phototropism in Sporangiophores of Phycomyces blakesleeanus - Grolig, Franz (American Society of Plant Physiologists, 2000)
The interaction between gravitropism and phototropism was analyzed for sporangiophores of Phycomyces blakesleeanus. Fluence rate-response curves for phototropism were generated under three different conditions: (a) for stationary sporangiophores, which reached photogravitropic equilibrium; (b) for sporangiophores, which were clinostated head-over during phototropic stimulation; and (c) for sporangiophores, which were subjected to centrifugal accelerations of 2.3g to 8.4g. For blue light (454 nm), clinostating caused an increase of the slope of the fluence rate-response curves and an increase of the maximal bending angles at saturating fluence rates. The absolute threshold remained, however, practically unaffected. In contrast to the results obtained with blue light, no increase of the slope of the fluence rate-response curves was obtained with near-ultraviolet light at 369 nm. Bilateral irradiation with near-ultraviolet or blue light enhanced gravitropism, whereas symmetric gravitropic stimulation caused a partial suppression of phototropism. Gravitropism and phototropism appear to be tightly linked by a tonic feedback loop that allows the respective transduction chains a mutual influence over each other. The use of tropism mutants allowed conclusions to be drawn about the tonic feedback loop with the gravitropic and phototropic transduction chains. The results from clinostating mutants that lack octahedral crystals (implicated as statoliths) showed that these crystals are not involved in the tonic feedback loop. At elevated centrifugal accelerations, the fluence-rate-response curves for photogravitropic equilibrium were displaced to higher fluence rates and the slope decreased. The results indicate that light transduction possesses a logarithmic transducer, whereas gravi-transduction uses a linear one.